Improving Plant Drug Yield -A Study of the Hyoscine: Hyoscyamine Ratio in a Datura Hybrid (Journal of Science and Technology, 2016)
The rapid depletion of drug plants in the wild due to uncontrolled exploitation has made it necessary to search for means of maximizing the yields and contents of drug plants. The potentiality of hybridisation as one of such means was investigated in Datura. The alkaloid content, the hyoscine: hyoscyamine ratio of the F1 hybrid, D. stramonium X D. ferox, was examined. Although the hybrid demonstrated hybrid' vigor (increased yield) the alkaloid content was lower than the higher alkaloid yielding parent D. ferox.